Histological Effects of Excessive Consumption of Zingeber officinale on Liver and Spleen of the Mice - Amer, Nusaibah; Khuder, Marwa H; Yacoub, Silva A; Baker, Noor N (Al-Nahrain Journal of Science, 2013)
الخلاصة: Ginger (Zingeber officinale) is a natural dietary component with antioxidant and anti-inflammation. In the present study, the influence of ginger ethanol extract on liver and spleen of mice was investigated. The animals were divided in to four groups then treated with different concentrations of ginger extract (0, 50, 75, 100 mg/ kg) for 10 days, and then the animals scarified to evaluate histological change on liver and spleen. Results showed that liver section of mice treated with (50 mg/kg) of extract exhibited no clear pathological lesion with the presence of moderate of kuppfer cell. While the sectional liver treated with (75 mg/kg) of extract showed double nuclei and proliferation of cells. Aggregation of mononuclear cells mainly macrophage and lymphocyte in liver parenchyma was observed in liver section of mice treated with (100 mg/kg) of extract. Spleen section of mice treated with (50 mg/kg) of extract showed hyperplasia of red pulp with proliferation with mononuclear cell around sinusoid form cord like structure. While, the sectional spleen treated with (75 mg/kg) of extract showed moderate hyperplasia of white pulp. Moderate peri-arterial hyper plasma and aggregate of lymphocyte and mononuclear cells in red pulp was notes in spleen section of mice treated with (100mg/kg) of extract.